2024
DOI: 10.1111/wrr.13148
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant signalling‐selective activated protein C that lacks anticoagulant activity is efficacious and safe in cutaneous wound preclinical models

Ruilong Zhao,
Meilang Xue,
Haiyan Lin
et al.

Abstract: Various preclinical and clinical studies have demonstrated the robust wound healing capacity of the natural anticoagulant activated protein C (APC). A bioengineered APC variant designated 3K3A‐APC retains APC's cytoprotective cell signalling actions with <10% anticoagulant activity. This study was aimed to provide preclinical evidence that 3K3A‐APC is efficacious and safe as a wound healing agent. 3K3A‐APC, like wild‐type APC, demonstrated positive effects on proliferation of human skin cells (keratinocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The study on mice found that lowering wound size led to increased epithelial division. Local application of BV reduces wound size in animal models ( Zhao et al, 2024 ). BV is used in wound dressing alongside polyvinyl alcohol and chitosan.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…The study on mice found that lowering wound size led to increased epithelial division. Local application of BV reduces wound size in animal models ( Zhao et al, 2024 ). BV is used in wound dressing alongside polyvinyl alcohol and chitosan.…”
Section: Medical Applicationsmentioning
confidence: 99%